Social innovation for community building through technology simplification - Mohd Mustafah, Anas (Malaysian Society of Agricultural Engineers, 2019)
Social Innovation is a concept of promoting social development of a community through the introduction of innovation to promote the community to change for the better. The innovation here can be technological, economic, social or combinations of these that aims to improve the community standard of living. One way to start a social innovation is by understanding the problems of the community through experiential learning. A Social Innovation through Team Entrepreneurial Learning (SITEL) workshop was held in Kota Kinabalu, Sabah in June 2018 where one project focuses on stingless bee community in Kg. Mitabang, Kiulu. Through experiential learning of living, discussing and befriending the community, a project was born to help the community to improve their stingless bee honey production by the introduction of homemade stingless bee honey pump. The technology simplification uses items obtainable from local hardware store and aquarium shop to build the pump that could be self-made and self-maintained by the community through a training video. The feedback from the community was positive after the initial introduction of the pump where they are reporting honey production every two weeks compared to months prior to using the pumps.